Discovery of unique mitotic mechanisms in Paradiplonema papillatum - Bungo Akiyoshi; Drahomíra Faktorová; Julius Lukeš (Open Biology)
Diplonemids are highly diverse and abundant marine plankton with significant ecological importance. However, little is known about their biology, even in the model diplonemid Paradiplonema papillatum whose genome sequence is available. Examining the subcellular localization of proteins using fluorescence microscopy is a powerful approach to infer their putative function. Here, we report a plasmid-based method that enables YFP-tagging of a gene at the endogenous locus. By examining the localization of proteins whose homologs are involved in chromosome organization or segregation in other eukaryotes, we discovered several notable features in mitotically dividing P. papillatum cells. Cohesin is enriched on condensed interphase chromatin. During mitosis, chromosomes organize into two rings (termed mitotic rings herein) that surround the elongating nucleolus and align on a bipolar spindle. Homologs of chromosomal passenger complex components (INCENP, two Aurora kinases and KIN-A), a CLK1 kinase, meiotic chromosome axis protein SYCP2L1, spindle checkpoint protein Mad1 and microtubule regulator XMAP215 localize in between the two mitotic rings. In contrast, a Mad2 homolog localizes near basal bodies as in trypanosomes. By representing the first molecular characterization of mitotic mechanisms in P. papillatum and raising many questions, this study forms the foundation for dissecting mitotic mechanisms in diplonemids.